Caliz - Goldstein, Shevard; Rike, Gregory; Herbert, L. James; Ewing, Bryant ([Lugar de publicación no identificado] : Ultramedia Prod., 1990)
Narra la historia de un caliz que pasa de generación en generación.
Keywords: ADMINISTRACION -- CASOS